Policy Input on Human Rights Issues by the Supreme Judiciary in Pakistan: Application of Stage Model of Public Policy - SOHAIL, Ms. FATIMA; HUSSAIN, Dr. FIAZ; WASEEM, Dr. MUHAMMAD ASLAM (The journal of contemporary issues in business and government, 2021)
The researches have revealed the legislature as the policy or law-making body and the executive branch as the policy implementing body whereas the third pillar of the state, the judiciary, is considered as a legal institute working as an arbitrator in all legal matters. However, the increasing pieces of evidence depict that the judiciary not only acts as an arbitrator in all legal controversies but also plays a role in public policymaking and politics. It is one of the official actors that plays its role in policy processes. This paper examines the role of the Supreme Court of Pakistan (SCP) in generating policy input at different stages of policy making. Content and thematic analysis methods have been used on all judicial verdicts given by the SCP on Human Rights Cases (HRCs). The time period ranges from 2009 to 2019. Purposive sampling technique is utilized to draw a sample containing HRCs from the population of judicial verdicts given by SC during the last ten years. The analysis reveals that the Supreme Judiciary provides its policy input and impacts policy process. It has the power to play its significant role in policymaking by giving policy input in problem identification and agenda-setting, policy formulation, policy adoption, and policy evaluation. The policy input given by SCP should be utilized in an effective way to reduce human rights issues and alleviate the infringement of fundamental rights of the citizens of Pakistan.